Design and Implementation of UI/UX for the SPINTAR Website (One-Stop Information and Consultation Service) at the Central Bureau of Statistics of Sukabumi City - Rendika Febrian; Hermanto (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2026)
The development of digital public services requires government institutions to provide information systems that are accessible, efficient, and responsive to community needs. One important factor influencing the quality of digital services is the implementation of effective user interface (UI) and user experience (UX) design. This community engagement program was conducted at the Central Bureau of Statistics (BPS) of Sukabumi City and focused on the implementation of UI/UX design for the SPINTAR website (Integrated Information and Consultation Service). The program aimed to improve the usability and accessibility of digital statistical information and online consultation services for the public. The methods applied included user needs analysis, wireframe development, visual interface design, interactive prototyping using Figma, and coordination with the development team to support design implementation. A user-centered design approach was adopted to ensure ease of navigation, visual consistency, and accessibility in public digital services. The results show that the implementation of structured UI/UX design improved information clarity, navigation efficiency, and overall user experience of the SPINTAR website. This program contributed to enhancing the quality of digital public services at BPS Sukabumi City and demonstrated the practical role of UI/UX design in supporting community-oriented information systems